Valores de hemograma y perfil bioquímico en mono araña de la costa ateles fusciceps mantenidos en cautiverio - Baquerizo Becerra, Julio Horacio (2008)
The research was carried out in zoos in the province of Guayas. Historic Park in the canton Samborondón 1,5 km Esmeraldas Avenue and the rescue centre in Jambelí finances Jambelí, located in the canton Naranjal, the 105 km way Machala, in the province of Guayas, during the months of December until June 2008. The objectives were 1. To determine the values of blood and biochemical profile in Ateles fusciceps kept in captivity and 2. Develop croos reference tables with the values obtained. Samples were taken from 22 specimens representing 100% of all existing population in captivity. Prior to obtain the sample to be anesthetized monkey, we will identify and proceeded to sample extraction of the femoral vein that is the most indicated for the extraction occurs in primates, the animal was put on his back and was located through the femoral pulse palpation. We do puncture the vein with a syringe needle with its previously charged with EDTA for biometría hemática for biochemistry and is used blood serum and the amount of 6 ml. Blood samples were collected CHELSIER led the clinical laboratory located in the neighborhood Atarazana Mz. 1-3 office 1. In this place were determined parameters of hemoglobin (g/l), hematocrit (1/1), leukocyte count (10^9/1), erythrocyte count (10^12/1), platelet count (10^12/1), and hemato indices: corpuscular volume medium (VCM), concentration mean cellular hemoglobin (MCHC), and corpuscular volume medium (VCM). The biochemistry is determined urea, creatinine, apparatus aminotransferase (AST), alanine aminotranferase (ALT), alkaline phosphatase (ALP), amylase and lipase. It established the values of values of blood. And these values were developing with reference table.